(untitled) (Research, Society and Development, 2022)
In the drug chain, the pharmacist and pharmacy attendants are the last contact between the health service and the user. These professionals are responsible for delivering the medication and providing guidance on treatment. Therefore, it is essential that there is adequate training and ongoing education for professionals in the sector. Permanent education in health is built from the daily problems seen collectively and from educational actions that seek alternatives and solutions for the transformation of health practices. The objective of the research was to verify the implementation and necessity of permanent education in health in outpatient and community pharmacies through articles recently published in the literature. For this, the method of integrative literature review was used through the Medline, Lilacs and Scielo databases. A total of 991 articles were found and 13 scientific productions were selected for full reading and synthesis, after applying the exclusion criteria. The literature does not specifically address the need for continuing education in community pharmacies for both pharmacists and other pharmacy professionals such as technicians or clerks. Most studies evaluate the results of continuing education for pharmacists. Although the concepts of permanent education and continuing education are confused, the need for permanent education and importance in the pharmacy environment is clear. Education increases the knowledge of professionals and generates greater confidence for both the worker and the patient, increasing the quality of care and drug dispensing.